The Targums : a critical introduction - Flesher, Paul Virgil McCracken. (Studies in the Aramaic Interpretation of Scripture, 2011)
The value and significance of the targums -translations of the Hebrew Bible into Aramaic, the language of Palestinian Jews for centuries following the Babylonian Exile-lie in their approach to translation: within a typically literal rendering of a text, they incorporate extensive exegetical material, additions, and paraphrases that reveal important information about Second Temple Judaism, its interpretation of its bible, and its beliefs. This remarkable survey introduces critical knowledge and insights that have emerged over the past forty years, including targum manuscripts discovered this century and targums known in Aramaic but only recently translated into English. Prolific scholars Flesher and Chilton guide readers in understanding the development of the targums; their relationship to the Hebrew Bible; their dates, language, and place in the history of Christianity and Judaism; and their theologies and methods of interpretation. "With clear presentation of current research and the issues involved, including the Targums and the New Testament, and a rich bibliography, this is the most complete-and up-to-date-introduction to the Targums. An outstanding, highly recommended achievement." Martin McNamara , Emeritus Professor of Scripture, Milltown Institute, Dublin, Ireland